Investigating the impact of a pharmacist intervention on inappropriate prescribing practices at hospital admission and discharge in older patients: a secondary outcome analysis from a randomized controlled trial - Beate Hennie Garcia; Katharina Kaino Omma; Lars Småbrekke; Jeanette Schultz Johansen; Frode Skjold; Kjell Hermann Halvorsen (SAGE Publishing, 2024)
Background: Inappropriate medication prescribing in older patients increases the risk of poorer health outcomes and increased costs. The IMMENSE trial, integrated a clinical pharmacist into the health care team, to improve medication therapy among older patients, and to investigate the impact on acute revisits to hospital. Objectives: This study investigated the prevalence of potentially inappropriate medications (PIMs) and prescribing omissions (PPOs) at hospital admission and discharge. It also explored the impact of the pharmacist intervention on PIMs and PPOs, and other factors associated with PIMs and PPOs at discharge. Design: The STOPP/START criteria version 2 were retrospectively applied at admission and discharge. PIM and PPO changes were compared, and Poisson regression was used to assess factors influencing prevalence at discharge. Results: At hospital admission, PIM prevalence was 58.6% among intervention patients and 64.8% among control patients. PPO prevalence was 55.3% and 55.5%, respectively. A larger proportion of PIMs identified at admission were resolved by discharge in the intervention group (42.9%) compared to the control group (27.4%). No difference was seen for PPOs. Poisson regression identified a significantly higher risk for PIMs at discharge in the control group compared to the intervention group (IRR 1.255; 95% CI 1.063-1.480, p  = 0.007), but no effect for PPOs. Patients living in a nursing home, a home care facility, or an institution showed a higher risk of PPOs at discharge compared to patients living at home (IRR 1.378; 95% CI 1.156-1.644, p  < 0.001). Conclusion: The IMMENSE intervention significantly reduced the risk of PIMs at discharge, with no effect on PPOs. Living in nursing homes, home care facilities, or institutions prior to hospitalization increased the risk of PPOs at discharge. Pharmacists may contribute to improved medication appropriateness in older hospitalized patients.